A PLL-free Roboust Control Scheme for Harmonic Current Compensation of Grid-Interfaced PV System Under Distorted Grid Voltages - Mishra M.K.; Lal V.N. (My University, 2025)
This paper presents a phase-locked loop (PLL) free robust control scheme for a single stage three-phase grid-interfaced photovoltaic (GIPV) system that does not requires a dedicated synchronization unit. Under the harmonically distorted grid voltages caused by nonlinear load the proposed control scheme utilizes an enhanced proportional multi-resonant (EPMR) current controller to effectively address the issue of grid current harmonics. The computational burden on the digital controller of the GCPV system reduces due to the elimination of a dedicated synchronization unit (PLL) in the proposed robust control scheme. The efficacy of the proposed robust control scheme is verified by experimentation in various grid scenarios, including situations with distorted grid voltages and changes in grid frequency. Moreover, a modified incremental conductance (MINC) maximum power point tracking (MPPT) algorithm is employed to minimize power fluctuations, especially when encountering rapidly changing atmospheric conditions. To assess the efficiency of the proposed robust control scheme, OPAL-RT simulator is employed. © 2023 IEEE.